Gender and environmental management in the wetlands of Bogotá - Gamboa-Arévalo, Adriana Patricia (Prospectiva. Revista de Trabajo Social e Intervención Social, 2019)
In the framework of gender studies, this article explores the beginning of the environmental movement for the conservation of Bogota’s wetlands from 1990 to 2009, with the aim of understanding the symbolic contents that order social relations and transform the environment. Furthermore, the study aims to contribute elements of reflection regarding the dynamics and tensions that the influence of gender binarism produces in the conservation of nature. In methodological terms, this reflection interweaves three threads: myth as an explanatory resource, the theory of gender and the accounts of those who formed the first community organizations for the defense of La Tibanica and La Conejera wetlands. The result of reviewing these aspects allows us to appreciate the complexity of the field in which gender relations unfold and to question the practices naturalized by culture that sometimes lead to common situations such as linking the destiny of women with motherhood, and consequently to expand the functions of vital care to the community and the environment. At other times, these practices lead to the reproduction of preservationist postures in environmental management that have a predominantly anthropocentric focus.